2006
DOI: 10.1186/1475-2883-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundAnopheles gambiae s.l. and An. funestus are important vectors of malaria and bancroftian filariasis, which occur as co-endemic infections along the Kenyan Coast. However, little is known about the occurrence and prevalence of concomitant infections of the two diseases in mosquito and human populations in these areas. This study reports the prevalence of concomitant infections of Plasmodium falciparum and Wuchereria bancrofti in mosquito and human populations in Jilore and Shakahola villages in Malind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…and An.funestus , and they occur year-round with peaks of population abundance coinciding with seasonal rains (Mbogo et al 2003, Mutuku et al 2011). The same mosquitoes transmit LF with an added role for Culex quinquefasciatus (Say) (Diptera: Culicidae) (Bögh et al 1998; Muturi et al 2006a,b). The current estimated population for Msambweni and Kwale districts is 288,000 and 152,000, respectively, totaling ≈440,000 (Kenya National Central Bureau of Statistics 2009).…”
Section: Methodsmentioning
confidence: 99%
“…and An.funestus , and they occur year-round with peaks of population abundance coinciding with seasonal rains (Mbogo et al 2003, Mutuku et al 2011). The same mosquitoes transmit LF with an added role for Culex quinquefasciatus (Say) (Diptera: Culicidae) (Bögh et al 1998; Muturi et al 2006a,b). The current estimated population for Msambweni and Kwale districts is 288,000 and 152,000, respectively, totaling ≈440,000 (Kenya National Central Bureau of Statistics 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The co-occurrence of malarial and filarial parasites has been reported in endemic areas [25-28]. Unlike malaria, filariasis, a neglected disease, is rarely fatal but severe morbidity, including disabilities and adverse economic consequences due to disfigurement of limbs and male genitals (elephantiasis and hydrocele, respectively), occurs in 40% of infected individuals [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 54 experiments conducted on laboratory mice investigating the effects of helminth infection on microparasite density suggested that the effect of interactions is dependent on the species pair [11], although none of the studies considered Wuchereria bancrofti (LF) and Plasmodium (malaria) co-infection. However, it is thought that infection with W. bancrofti increases mosquito susceptibility to Plasmodium infection, since migration of microfilariae disrupts the midgut, allowing Plasmodium easier access through the midgut to the salivary glands [3], [5], [29], [30]. On the other hand, mosquitoes carrying worm parasites have been found to reduce Plasmodium infectivity, with such vectors possessing a lower infection intensity compared to uninfected mosquitoes [31].…”
Section: Introductionmentioning
confidence: 99%